Openness to Innovations of the Regional Agro-Industry as a Subjective Factor of Innovative Activity - Neganova, Valentina Petrovna; Dudnik, Aleksey Vyacheslavovich (Economy of Regions, 2019)
The long-standing efforts of the agro-industry management to enhance the innovative processes resulted in more than modest innovative activity of their participants. The study assesses the openness to innovations of top managers and owners of the agroindustrial enterprises in Kurgan Oblast. We based the research on the thesis on the existence of a set of factors hampering innovative activity of the agro-industry, including subjective and socio-psychological factors. Moreover, we hypothesise that human factors play the decisive role in solving the problem of innovations’ implementation (or non-implementation). Underestimation of innovations’ role in the development of the managed system, main stakeholders’ resistance to innovations’ implementation cause agro-industry’s deceleration and implementation of the very conservative, inertial, extensive scenarios. We tested the hypothesis using a representative sample survey of top managers and owners of the small- and medium-sized agro-industrial enterprises. Using the standardised methodology of psychological testing of the main components of openness to innovations, we assessed an overall level of openness to innovations as fairly low. Organizational openness appeared to be the most problematic component, especially in comparison with relatively high values of personal and cognitive openness. For increasing innovative activity of the agro-industrial enterprises, we recommend state authorities, which regulate competitiveness, to use a more direct approach and the system of economic incentives for innovative behaviour. This system of incentives should include a system of standards of innovative activity that in case of failure would block the organization’s access to the programs of the agro-industry’s state support. The study’s results can be used in scientific research on the innovative activity of the regional agro-industry and in educational process of the field-oriented universities.